Penerapan Media dan Teknologi Digital Pendidikan dalam Pembelajaran di SD Tahfizh Al-Qur’an Jabal Rahmah - Nur Fajriah, Fellisa Juliana; Haryadi, Zalfa Shabrina; Lestari, Ambar Sri (CV. ITTC INDONESIA, 2025)
Education has undergone significant transformation in the era of advancing information and communication technology, presenting both new opportunities and challenges. This study aims to describe the use of digital media and technology in the learning process at SD Tahfizh Al-Qur’an Jabal Rahmah, identify the obstacles faced, and explore strategies for optimizing their use. A descriptive qualitative method was employed, with data collected through triangulation techniques involving interviews, observations, and document analysis. The findings indicate that the use of digital media and technology remains limited due to inadequate infrastructure, school policies prohibiting the use of mobile phones, and the low level of digital literacy among teachers and parents. Nevertheless, some teachers have started using media such as videos, Quizizz, and PowerPoint presentations. The school demonstrates a commitment to digital transformation through plans to develop a digital library, computer lab, and digital Qur’an lab. To enhance the effective use of technology, teacher training, adequate facilities, and the involvement of all stakeholders are essential to ensure technology integration aligns with the needs of elementary-level students.